ID167 Determinantes para alto-custo de pacientes em UTIs no Brasil - Daniel Tavares Malheiro; Kaue Capellato Junqueira Parreira; Isabella Lott Bezerra; Antonio Paulo Nassar Junior; Adriano Jose Pereira; Vanessa Damazio Teich (Jornal de Assistência Farmacêutica e Farmacoeconomia)
Introdução